1997
DOI: 10.1006/anbo.1997.0496
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Light and Temperature on Competition between Atrazine Susceptible and ResistantBrassica rapa

Abstract: Biotypes of Brassica rapa susceptible (S) and resistant (R) to atrazine were grown in competitive replacement series in all possible combinations of two light levels and three temperature regimes in controlled growth cabinets. Photosystem II function was investigated in all conditions by fluorescence-induction techniques. There were no significant differences in the dry weight of the two biotypes when grown in pure stands. In pure stands both biotypes produced more biomass under the high light level. Under hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 40 publications
2
16
0
1
Order By: Relevance
“…An interaction between temperature and light levels in the competitive outcome between triazine-tolerant and triazine-susceptible rapid-cycling domesticated B. rapa was observed. At low light and high temperatures, the resistant biotype was a better competitor than the susceptible biotype (Plowman and Richards 1997). Friesen et al (2003) examined 27 commercially available certified seedlots of conventional B. napus for contamination with herbicide-resistant seed.…”
Section: Herbicide Resistancementioning
confidence: 99%
“…An interaction between temperature and light levels in the competitive outcome between triazine-tolerant and triazine-susceptible rapid-cycling domesticated B. rapa was observed. At low light and high temperatures, the resistant biotype was a better competitor than the susceptible biotype (Plowman and Richards 1997). Friesen et al (2003) examined 27 commercially available certified seedlots of conventional B. napus for contamination with herbicide-resistant seed.…”
Section: Herbicide Resistancementioning
confidence: 99%
“…It is now widely accepted that the resistance of plants to triazines, caused by the specific mutation(s) at the Q B site of the D1 protein, is associated not only with the lowered efficiency of photosynthetic electron transport but also with the increased sensitivity of plants to photoinhibition and the decreased efficiency of some protective processes (e.g. the light-induced formation of zeaxanthin) (Darko et al 1996, Plowman and Richards 1997, Devine and Shukla 2000, Kumata et al 2001, Szigeti and Lehoczki 2003, Varadi et al 2003. The triazinesusceptible biotypes are therefore usually better adapted to the growth under high light conditions compared to the resistant ones.…”
Section: Resultsmentioning
confidence: 99%
“…The triazinesusceptible biotypes are therefore usually better adapted to the growth under high light conditions compared to the resistant ones. Plowman and Richards (1997), who examined the effect of high and low light and three temperature regimes on atrazine-susceptible and -resistant Brassica rapa, have found that under high light conditions the susceptible biotype showed a greater photon yield and relative competitive ability than the resistant biotype when grown at high or medium temperatures, but at low temperature the situation was reverse. Under low light conditions, the chlorophyll fluorescence parameters of both biotypes did not differ in either temperature regime examined, which agrees well with our results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Plowman and Richards (1997) conducted a study comparing competitive ability between resistant and susceptible biotypes of Brassica rapa. Their study consisted of two light levels and three temperature treatments.…”
Section: Introductionmentioning
confidence: 99%